Android Wireless Application Development Volume II : Advanced Topics, Third Edition - Darcey, Lauren; Conder, Shane (Addison-Wesley Professional, 2012)
Android Wireless Application Development has earned a reputation as the most useful real-world guide to building robust, commercial-grade Android apps. Now, authors Lauren Darcey and Shane Conder have systematically revised and updated this guide for the latest Android SDK and tools updates. To accommodate their extensive new coverage, they've split the book into two leaner, cleaner volumes. This Volume II focuses on advanced techniques for the entire app development cycle, including design, coding, testing, debugging, and distribution. Darcey and Conder cover hot topics ranging from tablet development to protecting against piracy and demonstrate advanced techniques for everything from data integration and UI development to in-app billing. Every chapter has been thoroughly updated to reflect the latest SDKs, tools, and devices. The sample code has been completely overhauled and is available for download on a companion website. Drawing on decades of in-the-trenches experience as professional mobile developers, the authors also provide even more tips and best practices for highly efficient development. This new edition covers Advanced app design with async processing, services, SQLite databases, content providers, intents, and notifications Sophisticated UI development, including input gathering via gestures and voice recognition Developing accessible and internationalized mobile apps Maximizing integrated search, cloud-based services, and other exclusive Android features Leveraging Android 4.0 APIs for networking, web, location services, the camera, telephony, and hardware sensors Building richer apps with 2D/3D graphics (OpenGL ES and RenderScript), animation, and the Android NDK Tracking app usage patterns with Google Analytics Streamlining testing with the Android Debug Bridge This book is an indispensable resource for every intermediate- to advanced-level Java developer now participating in Android development and for every seasoned mobile developer who wants to take full advantage of the newest Android platform and hardware. Also look for: Android Wireless Application Development, Volume I: Android Essentials.